2013
DOI: 10.9775/kvfd.2013.9215
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and Histopathological Findings of Chondrosarcoma in Mammary Gland of A Dog: A Case Report

Abstract: SummaryChondrosarcoma is a malignant tumor of chondrocytes and occurs most commonly on the flat bones and the nasal cavity. Mammary chondrosarcoma is an uncommon tumor in canine practice. The aim of present paper is to report a case of mammary chondrosarcom in a 10-year-old German shepherd bitch. The dog with a mass in her right caudal thoracic mammary gland which grown gradually in 8 months, was referred to the veterinary teaching hospital. The mass and local lymph nodes were resected by complete mastectomy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, the researchers did not state the exact lobular localization of the tumoral mass in previous studies [5,9,10,14,21] . Golshahi et al [22] have used streptavidin-biotin-peroxidase technique for IHC of ERα for chondrosarcoma in mammary gland of a dog and they found this tumour was not expressed ERα like most of the cases in this study. Toniti et al [20] used ER and PR like in this current study but they used it in different dilutions and they concluded that immunohistochemical studies did not have any correlation to estrogen and/or progesterone receptors expressions in canine mammary tumours.…”
Section: Discussionmentioning
confidence: 50%
“…However, the researchers did not state the exact lobular localization of the tumoral mass in previous studies [5,9,10,14,21] . Golshahi et al [22] have used streptavidin-biotin-peroxidase technique for IHC of ERα for chondrosarcoma in mammary gland of a dog and they found this tumour was not expressed ERα like most of the cases in this study. Toniti et al [20] used ER and PR like in this current study but they used it in different dilutions and they concluded that immunohistochemical studies did not have any correlation to estrogen and/or progesterone receptors expressions in canine mammary tumours.…”
Section: Discussionmentioning
confidence: 50%